HUBUNGAN PEKERJAAN, PARITAS PUS TENTANG KONTRASEPSI DENGAN PEMILIHAN KB SUNTIK - Winda Maulina Sari Nasution; Rhina Chairani Lubis; Febri Yusnanda; Tika Ayu Pratiwi; Lili Nurmaliza (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
According to the 2021 Indonesia Health Profile, there are 6,868,882 new registered family planning participants and 24,258,531 active family planning participants in Indonesia alone, which has 38,343,931 couples of childbearing age. Injection contraception is the most widely used in Indonesia, followed by the pill (17.24%), IUD (7.35%), implants (7.40%), female operating method (MOW) (2.76%), condoms (1, 24%), and MOP (0.50%). (RI Ministry of Health, 2021). This study aims at Employment Relations, PUS Parity regarding Contraception with the Selection of INJECTION KB. This research is a descriptive quantitative analytic study through a cross-sectional approach with the chi-square test taken from secondary data of 50 populations and samples. The test results obtained a p value (0.009) which means there is a relationship between work knowledge, PUS parity regarding contraception and the choice of INJECTION KB